IJFSNR 2019
DOI: 10.31546/ijfsnr.1001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Restrictions and Malnutrition on Morphological Construction of Bone Marrow

Abstract: Well-balanced diet impacts on nutritional status. It is an important factor which determines proper forming of haematopoietic cells of bone marrow. Deficit as well as excess of diet components or calories can disturb functions of bone marrow and cause development of many diseases, including anaemia. The review of actual knowledge on the influence of dietary restrictions and malnutrition on functions of haematopoietic stem cells and erythrogenesis has been done in this paper. It was conducted many researches re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…This effect was potent and rapid and mediated anticarcinogenic effects [ 89 ]. It was also shown that moderate caloric restriction could contribute to slow down in aging and to prevent chronic diseases [ 90 ]. In murine models, studies showed that DR-induced delayed aging and retarded tumor development were attributed to induction of apoptosis to selectively eliminate preneoplastic and superfluous cells that negatively affected normal function and promote cell transformation [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was potent and rapid and mediated anticarcinogenic effects [ 89 ]. It was also shown that moderate caloric restriction could contribute to slow down in aging and to prevent chronic diseases [ 90 ]. In murine models, studies showed that DR-induced delayed aging and retarded tumor development were attributed to induction of apoptosis to selectively eliminate preneoplastic and superfluous cells that negatively affected normal function and promote cell transformation [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ensuring adequate protein intake, especially from high-quality sources, is critical to combat stunting and promote optimal growth and development in children. Interventions aimed at increasing protein intake, whether through dietary diversification, supplementation, or fortification, can make a significant contribution to efforts to combat stunting and its associated health consequences (Kozak & Krośniak, 2019).…”
Section: Figure 2 Patin Fish (Pangasius Hypophthalmus) Protein Concen...mentioning
confidence: 99%
“…In the hospital outpatient setting, nutritional risk differs between 13-28% depending on diagnosis and amount of weight loss used to define UWL [38][39][40][41][42]. In Danish outpatients with COPD, 13.4% were found with five % weight loss within two months.…”
Section: Frequency and Consequences Of Malnutrition And Nutritional Riskmentioning
confidence: 99%